Integrating National Oral Health Programme and National Tobacco Control Programme in India: a concept for policy coherence - Pai, Mithun; Yellapurkar, Shweta; Sarit, Swapna; Pentapati, Kalyana C.; Avinash, Badekkila Ramachandra; Shenoy, Ramya (Frontiers in Oral Health, 2025)
IntroductionTobacco use continues to be a major risk factor for morbidity and mortality worldwide. At least 8.71 million fatalities were attributed to tobacco use, according to recent estimates from the Global Burden of Disease. Tobacco has a detrimental influence on oral health, such as oral cancer, periodontal disease, periimplantitis, and implant failure. This comparative analysis explores the potential integration of two programs—the National Oral Health Programme (NOHP) and the National Tobacco Control Programme (NTCP)—that are closely linked with each other.Possible blueprint for integrating NOHP and NTCP in Indiajoint awareness campaigns implementing a common risk factor approach, integrated screening and cessation services with dental colleges as tobacco cessation hubs, integrated oral cancer and tobacco screening as part of routine dental screening, and combination of monitoring and surveillance of tobacco usage and oral health.Challenges in integrating the NOHP and NTCPBoth the NOHP and NTCP face resource constraints relating to funding, human personnel, and infrastructure. These two initiatives are administered by separate branches within the health sector, involving different stakeholders with conflicting interests. There is a lack of unified data systems that provide a ground for comparing the effects of tobacco on oral health and integration of this data. The stigma associated with tobacco use: Tobacco users may be reluctant to associate themselves with oral health programs.ConclusionIntegrating the National Oral Health Programme and National Tobacco Control Programme in India can address the dual burden of tobacco use and oral health, by leveraging the strengths of both programs, which include educating trainers, raising awareness about oral health and tobacco use, improving access to trained manpower particularly dentists with dual roles, and promoting policy changes.